Peaks of faith : Protestant mission in revolutionary China - Tian, Rukang. (Studies in Christian Mission, 1993)
This is a pioneering study of the impact of Christianization among the Chinese. Focusing primarily on the minority peoples of Yunnan province, it nonetheless fully mirrors the historical development of the Protestant mission in China. Drawing on many years of observation in the field and upon a comprehensive consultation of official documents relating to Christians on the mountain peaks, the study chronicles how the early foreign missionaries, thanks to their self-sacrifice and the examples they set of religious zeal, cemented the hitherto segregatory and leaderless tribes together, vigorously shaking the desolate mountain folk out of their age-long isolation. It was the trend of the time to identify Christianity as the desirable agent to promote socio-economic change in the undeveloped communities. This is a timely original contribution to the historical study of the Christian missionary enterprise and the pressing problem of freedom of worship that currently exists in China.